Inovasi Manajemen Pemerintahan Berbasis Aplikasi Digital di Provinsi Jawa Tengah - Arif Sofianto (Research and Development Agency Ministry of Home Affairs, 2019)
The Government of Central Java Province developed digital applications in order to support bureaucratic reform, namely the Government Resources Management System (GRMS) and electronic-based personnel management aplication system. The purpose of this paper is to analyze the use of the application, what are the constraints and how development is needed. This research is in the form of analytical descriptive, with a qualitative approach. Primary data collect from system users, and secondary data are from the application system. Data analysis was performed with simultaneous models developed by Miles and Huberman. The existence of the GRMS application system and the application of the personnel information system so far has been enough to contribute to the improvement of government performance, which is to facilitate local government administrators. On the other hand, application usage is hampered by the readiness of users, there is no synchronization between applications, and application performance is not optimal. The conclusion of the research is that government management innovations in the form of GRMS applications and personnel management aplication system have been carried out in assisting the administration of government. The existence of these applications can encourage changes in work culture, which contributes to bureaucratic reform. The obstacle faced is the readiness of the authorities because they are not used to using digital systems, their behavior and work habits. Another obstacle is the still not optimal role of the application system to support all government management activity needs, as well as the integration between applications. The change needed is to build integration between applications as a system that is interrelated, so as to increase transparency, efficiency, responsibility and ease of control.